Angela Merkel’s Views On 2015 Open Door Policy and Its Implications with The Future of der Panzer Deutschland: Indonesia - Azzahra, A. Qalbi Faathimah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2024)
Germany, the head of the European Union, enacted measures that were notably different from those of other members when Europe was beset by the immigration crisis in 2015. Germany freely opened its borders with the Open Door Policy, which was overseen by Angela Merkel, to allow migrants to enter its land. Unfortunately, this strategy was met with several objections and rejections from different groups. Public figures, opposition parties, Merkel's own party, interest groups, and the European Union as a regional governing body for Germany were among them. This policy wasn't decided upon democratically, nor did it involve the involvement of the Bundestag (level I parliament). Merkel steadfastly defended and implemented her divisive strategy in the face of numerous criticisms. This viewpoint shows the distinct perspective or impression that Merkel had when she created the Open Door Policy in response to the immigration crisis. This essay will explain how Angela Merkel's vision of the world may have influenced her decision to protect migrants while encountering various types of opposition. The belief and image systems influenced Angela Merkel's perception that Germany should be the primary actor in responding to the refugee crisis that occurred in the European Union region and around the world, it was discovered using Ole R. Holsti's framework for the relationship between perception and decision-making. This article also looking forward on how Germany could face the immigration problems in the future. Keywords: Angela Merkel, Germany, Open Door Policy, Holsti